Determinan Pemilihan Alat Kontrasepsi Intrauterin pada Wanita Usia Subur di Puskesmas Kuta Baro Kabupaten Aceh Besar - Aiman, Ummu; Salamah, Salamah; Fazlaini, Risna; Zaitun, Zaitun; Muliana, Muliana (Public Health Journal, 2026)
The National Family Planning (FP) program aims to improve the quality of human resources through the use of contraceptive methods. The Intrauterine Device (IUD) is a long-term contraceptive method that is safe and highly effective compared to other methods. This study aimed to identify factors associated with the selection of IUD contraceptives among women of reproductive age. This research employed a descriptive analytic design with a cross-sectional approach. The independent variables included education level, knowledge, socio-cultural factors, and attitude, while the dependent variable was the use of IUD. The study was conducted at the Kuta Baro Public Health, from April 13 to April, 2026, with a sample of 86 respondents selected using purposive sampling. The results showed a significant relationship between education level (p=0.024), knowledge (p=0.034), and attitude (p=0.008) with the selection of IUD. Meanwhile, socio-cultural factors were not significantly associated (p=0.233). In conclusion, education level, knowledge, and attitude play important roles in the selection of IUD contraceptives, while socio-cultural factors do not show a significant relationship. It is recommended that healthcare providers enhance education and counseling regarding IUD to improve knowledge and positive attitudes among women of reproductive age, and that the community actively seek accurate information about contraceptive methods